The Effects of Transformational Leadership and Work-Life Balance on Employee Performance at PT. Pan Putra Samudra - Abdullah Syafi'i; Ade Solahudin (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of transformational leadership and work-life balance on employee performance at PT Pan Putra Samudra Cirebon. The research method used is an associative quantitative approach with data collection techniques through a Likert-scale questionnaire to 145 respondents who are company employees. Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (SEM-PLS) to test the validity, reliability, and relationships between variables. The results show that transformational leadership has a positive and significant effect on employee performance with a t-statistic value of 5.582 and a path coefficient of 0.378. In addition, work-life balance also has a positive and significant effect on employee performance with a t-statistic value of 3.989 and a path coefficient of 0.315. Simultaneously, both variables are able to explain employee performance with an R-square value of 0.353, which is included in the moderate category. This indicates that inspirational leadership and balance between work and personal life are important factors in improving employee performance. Thus, companies are advised to develop transformational leadership styles and work-life balance policies on an ongoing basis.